2013 Africon 2013
DOI: 10.1109/afrcon.2013.6757817
|View full text |Cite
|
Sign up to set email alerts
|

Mobile device localization in IEEE 802.11 networks: A comparative analysis of SSDoA against TDoA

Abstract: This work focuses on benchmarking the "Time Difference on Arrival (TDoA)" algorithm against the relatively novel one, "Signal Strength Difference on Arrival (SSDoA)" in the context of mobile positioning in IEEE 802.11 (WLAN) networks. TDoA is a localization technique which has a proven track record, being at the heart of many commercial wireless geolocation applications. In an attempt to validate the potential application of SSDoA for indoor localization, we devise a representative mathematical model and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In this methodology, sensor tag determines its own location which means system up time is relatively longer and as a result battery life of sensor tag is shorter [62]. WiFi finger-print based localization utilizing low-power radio; however, the accuracy of system was proven to be 85% with localization accuracy of room level and 60% energy consumption improvement compared to utilizing WiFi interfaces [65]. Wireless Local Area Network (WLANs) that are built on top of IEEE 802.11 standard compliance generally consume excessive amount of battery.…”
Section: Trust Based Localization Protocol (Trustlp)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this methodology, sensor tag determines its own location which means system up time is relatively longer and as a result battery life of sensor tag is shorter [62]. WiFi finger-print based localization utilizing low-power radio; however, the accuracy of system was proven to be 85% with localization accuracy of room level and 60% energy consumption improvement compared to utilizing WiFi interfaces [65]. Wireless Local Area Network (WLANs) that are built on top of IEEE 802.11 standard compliance generally consume excessive amount of battery.…”
Section: Trust Based Localization Protocol (Trustlp)mentioning
confidence: 99%
“…Various methodologies introduced by other peers that address such issue. For example, a methodology introduced where utilizing IEEE 802.11 Another IEEE 802.11 methodology introduced to localize the location of a mobile tag is to utilize Angle Difference of Arrival (ADOA), Time Difference of Arrival (TDOA), Signal Strength Difference of Arriva (SSDOA)[65]. Based on various tests performed it is concluded that as number of anchor nodes increase, the localization accuracy and reliability increase as well which means system latency increases and network scalability become more difficult.…”
mentioning
confidence: 99%
“…In this methodology, sensor tag determines its own location which means system up time is relatively longer and as a result battery life of sensor tag is shorter [62]. WiFi finger-print based localization utilizing low-power radio; however, the accuracy of system was proven to be 85% with localization accuracy of room level and 60% energy consumption improvement compared to utilizing WiFi interfaces [65]. Wireless Local Area Network (WLANs) that are built on top of IEEE 802.11 standard compliance generally consume excessive amount of battery.…”
Section: Trust Based Localization Protocol (Trustlp)mentioning
confidence: 99%
“…Various methodologies introduced by other peers that address such issue. For example, a methodology introduced where utilizing IEEE 802.11 Another IEEE 802.11 methodology introduced to localize the location of a mobile tag is to utilize Angle Difference of Arrival (ADOA), Time Difference of Arrival (TDOA), Signal Strength Difference of Arriva (SSDOA)[65]. Based on various tests performed it is concluded that as number of anchor nodes increase, the localization accuracy and reliability increase as well which means system latency increases and network scalability become more difficult.…”
mentioning
confidence: 99%